2021
DOI: 10.1039/d0cc07969c
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum-incorporated β-Ni(OH)2 nanoarrays for robust urea electro-oxidation

Abstract: A novel electrocatalyst exhibits superior catalytic activity contributed to its optimized electronic structure, downshift of its d-band center and well-exposed active sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The significantly lower Ni 2+ /Ni 3+ redox potential of 1.33 V vs. RHE observed for PA-NF strongly suggested that the surface reconstruction and NiOOH formation became easier after PA coordination. 6,24 Then, we further quantified the in situ formed NiOOH by integrating the j vs. E curves from CV. 25 The integrated charge of the PA-NF electrode was 5.28 times larger than that of the NF electrode, indicating that PA coordination led to acceleration of the surface reconstruction and enrichment of NiOOH catalytic intermediates during the reaction.…”
mentioning
confidence: 99%
“…The significantly lower Ni 2+ /Ni 3+ redox potential of 1.33 V vs. RHE observed for PA-NF strongly suggested that the surface reconstruction and NiOOH formation became easier after PA coordination. 6,24 Then, we further quantified the in situ formed NiOOH by integrating the j vs. E curves from CV. 25 The integrated charge of the PA-NF electrode was 5.28 times larger than that of the NF electrode, indicating that PA coordination led to acceleration of the surface reconstruction and enrichment of NiOOH catalytic intermediates during the reaction.…”
mentioning
confidence: 99%
“…8(a), the spin-splitting phenomenon is present in both the α and β phases of NiMoO 4 . Besides, the bandgap of β-NiMoO 4 is about 1 eV smaller than that of α-NiMoO 4 both spin up and spin down, suggesting that β-NiMoO 4 possesses better conductivity 50 (Fig. 8(b)).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the anode current density presented a dramatic increase in the LSV curves for the CoNiFeS–OH nanostructures after the introduction of urea. We ascribed this phenomenon to the ureaoxidation, 44 owing to the significantly lower energy required for urea oxidation than that of H 2 O oxidation. Moreover, we also varied the concentration of urea during electrocatalysis and determined the optimal urea concentration (0.33 M) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…15,43 The peak at 532.7 eV was assigned to the H 2 O molecules, which were physically and chemisorbed on the structural surface. 7,44 Noticeably, the strong peak at 531.5 eV was attributed to the typical bonds between metal and -OH (denoted as M-OH, M = Co, Ni, Fe). 25,45 Accordingly, the contents of M-OH, M-O, and H 2 O were determined to be 66.9%, 7.1%, and 26%, respectively, indicating that the M-OH was dominant.…”
Section: Characterizationsmentioning
confidence: 99%